The Study of End-User Computing Satisfaction (EUCS) on Computerised Accounting System (CAS) Among Public Universities : A Survey in Bursar's Office - Mohd. Rushdan, Yasoa' (2004)
There is wealth of literature in the area of the measurement of satisfaction among end user computing. Further, it has had a long history within the Information System (IS) field. Focusing in the area of end-user computing, a number of studies have attempted to capture the overall evaluation that end users have regarding the use of an information system. However, it seems clear that previous research have not attempted to test the End User Computing Satisfaction (EUCS) on the computerised accounting system (CAS) especially in public universities in general. The purpose of this study is to measure the level of EUCS among computerised accounting system end users in public universities. The study also evaluates the significance relationship between EUCS factors (content, accuracy, format, ease of use, timeliness, satisfaction with the system speed, system reliability) and the overall EUCS in Malaysian context. Further, the study also examines the significance differences of perception on overall EUCS among the other variables such as gender, education background, position, tenure and attending computerised accounting course. Finally, the study provides results from empirical test of these relationships. Tests are conducted using Pearson Correlation, T-test and ANOVA (Analysis of Variance). The empirical results of this study can provide support for the Doll and Torkzadeh EUCS model (1988). The overall results support all the hypotheses, which related to the factors contributing to the EUCS. However, the study found that there is no significance differences of perception on overall EUCS among gender, education background, position, tenure and attending computerised accounting course.